STRATEGI DIGITAL MARKETING TOKO BUAH DI KOTA MALANG (Digital Marketing Strategy Fruit Shop in Malang City) - RAHMAT MUDZAKIR HUSAYN; LIVIA WINDIANA; ARY BAKHTIAR (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2022)
Digital marketing is an alternative strategy in product marketing to make it easier for business actors to monitor and provide for the needs and desires of potential consumers. The purpose of this study is to analyze the internal factors that are the strengths and weaknesses of fruit shops in the city of Malang, analyze the external factors of fruit shops in the city of Malang, and analyze digital marketing strategies that can be carried out by fruit shops in the city of Malang. The data analysis method uses SWOT analysis to analyze internal factors (strengths and weaknesses) and external factors (opportunities and threats) that affect the digital marketing strategy of fruit shops in Malang City. The digital marketing strategy is in quadrant one, which is offensive, with the coordinates of point x being the coordinates of the IFAS strategy with the coordinates of 0.651, while the coordinates of point y are the coordinates of the EFAS strategy with the coordinates of 0.401, which are strategies that utilize internal strengths and external opportunities. The recommended alternatives include: Increasing interesting social media content ideas for wider promotion of online fruit shops.